TDP-43: From Alzheimer’s Disease to Limbic-Predominant Age-Related TDP-43 Encephalopathy - Huang, Wendi; Zhou, Yongjian; Tu, Lin; Ba, Zhisheng; Huang, Juan; Huang, Nanqu; Luo, Yong (Frontiers in Molecular Neuroscience, 2020)
Since the discovery of TAR DNA-binding protein 43 (TDP-43) in 1995, our understanding of its role continues to expand as research progresses. In particular, its role in the pathogenesis of Alzheimer's disease (AD) has drawn increasing interest in recent years. TDP-43 may participate in various pathogenic mechanisms underlying AD, such as amyloid β deposition, tau hyperphosphorylation, mitochondrial dysfunction and neuroinflammation. Because AD is complex and heterogeneous, and, furthermore, because of the distinct characteristics of TDP-43 that are mostly seen in the oldest-old and those with more severe clinical phenotype, subcategorization based on specific features or biomarkers may significantly improve diagnosis and treatment. AD-like cognitive dysfunction associated with TDP-43 pathology may therefore be a distinct encephalopathy, referred to as limbic-predominant age-related TDP-43 encephalopathy (LATE).